The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1088/0953-2048/21/6/065009
|View full text |Cite
|
Sign up to set email alerts
|

The nucleation and growth mechanism of the electrodeposition of Tl2Ba2Ca2Cu3O10superconducting thin films on Al-substrate

Abstract: The present study demonstrates the nucleation and growth mechanism of the Tl 2 Ba 2 Ca 2 Cu 3 O 10 (Tl-2223) superconductor by the electrodeposition technique on low cost aluminum coated glass (ALCG)-substrate at low processing temperature and short synthesis time, which is one of the most important aspects demanded of superconducting materials in practical applications. Superconducting thin films of Tl-2223 have been fabricated by the electrodeposition process on crystalline ALCG-substrate for the first time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the surface morphology of amorphous carbon films demonstrates the island groove characteristic of the non‐reactive nucleation, characterized by field emission SEM images in Fig. . As the complex reaction happens at the liquid/solid interface, which is hard to observe through the experimental techniques, although XPS and FTIR analysis support the formation of some Si–O–C and Si–C bonds at the interface, amorphous carbon films still remain weakly adhesive.…”
Section: Deposition Mechanismmentioning
confidence: 99%
“…Moreover, the surface morphology of amorphous carbon films demonstrates the island groove characteristic of the non‐reactive nucleation, characterized by field emission SEM images in Fig. . As the complex reaction happens at the liquid/solid interface, which is hard to observe through the experimental techniques, although XPS and FTIR analysis support the formation of some Si–O–C and Si–C bonds at the interface, amorphous carbon films still remain weakly adhesive.…”
Section: Deposition Mechanismmentioning
confidence: 99%
“…It has been shown that depending on the rate of nucleation, the growth mechanisms are of two types, instantaneous nucleation and progressive nucleation [7]. In order to study the electrochemical nucleation and growth mechanisms of YBaCuO electrodeposition onto AAO, the currenttime transients are further analyzed by plotting the (I/I max ) 2 versus (t/t max ) for the instantaneous and progressive growth.…”
Section: Resultsmentioning
confidence: 99%
“…In order to study the electrochemical nucleation and growth mechanisms of YBaCuO electrodeposition onto AAO, the currenttime transients are further analyzed by plotting the (I/I max ) 2 versus (t/t max ) for the instantaneous and progressive growth. A theoretical plot for the Scharifker and Hills model [7] and the experimental plots of YBaCuO alloy deposition are shown in Fig. 1b.…”
Section: Resultsmentioning
confidence: 99%
“…High temperature superconducting (HTS) thin film is a kind of important material used in superconducting electronics applications, including high-frequency electronic devices and Josephson junction devices [1]. In the practical HTS thin films, Tl 2 Ba 2 CaCu 2 O 8 (Tl-2212) films are getting more and more attention on passive microwave devices due to their high critical temperature [2][3][4], high critical current density, low microwave surface resistance and strong anti-humidity [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%